Categorização da estrutura de raciocínio clínico demonstrado por estudantes de medicina em escola médica brasileira, baseada na taxonomia solo - Camargos, Breno Gontijo de (2023)
Identifying the stage of development of clinical reasoning in which medical students find themselves at provides the professor with the opportunity to evaluate the appropriate strategy for learning this cognitive activity. This paper evaluates whether it is possible to categorize the structure of reasoning demonstrated by medical students, using the assumptions of the taxonomy SOLO - Structure of Observing Learning Outcome. To know the "SOLO level" at which the student is allows the formulation of better targeted objectives and the adoption of more appropriate teaching strategies. By creating instruments based on the learning categories of the SOLO taxonomy (superficial and deep), the professor can consciously control the students' instruction through assessments, activities and formative or summative interventions. Objectives: To analyze and classify the responses of medical students of the 6th, 9th and 12th terms, in the resolution of clinical cases, having as a parameter the SOLO Taxonomy levels. To determine the diagnostic scores of the answers provided and correlate the degree of complexity of clinical reasoning demonstrated by the students and the diagnostic accuracy. Materials and methods: This was a cross-sectional, descriptive study aimed at students of the 6th term (beginning of the clinical cycle), 9th term (beginning of internships) and 12th term (end of the course), regularly enrolled in the UNIFENAS/BH medical course. Each student analyzed a clinical case on Pulmonary Thromboembolism and another on Polycystic Ovary Syndrome. The answers were analyzed and classified using the SOLO Taxonomy. Results: Students of the 12th term showed greater cognitive complexity in solving cases compared to the students of the 6th term. There was a positive correlation between the level of cognitive complexity and the diagnostic accuracy obtained during the resolution of the cases. The percentage of correct diagnoses was more closely related to the SOLO category demonstrated by the students than to the term they found themselves at. Conclusion: The results showed that the categorization of the structure of clinical reasoning used by medical students during the resolution of clinical cases, through the SOLO Taxonomy, has acceptable reliability.